Reading Comprehension Problems among First and Second Year EFL Students at Shaikh Zayed University in Afghanistan - Rahmani, Saifurrahman; Shahab, Subhanullah; Mohabat, Gul Ahmad (Integrated Journal for Research in Arts and Humanities, 2023)
It is obviously clear that strong reading comprehension has a significant influence on students’ success at university. This study aims to investigate reading comprehension problems among first and second year EFL students at Shaikh Zayed University in Afghanistan. Fifty EFL first and second year students from the Department of English participated in the survey. The study used a random sampling design of a quantitative approach. The data were gathered through a five-point Likert scale style questionnaire adopted from Abu Abeeleh, Al-Ghazo, and Al-Sobh (2021). The data were analyzed through SPSS V.23 software to calculate the descriptive statistics, frequency, percentage and mean score. The results indicated that great majority of respondents agreed on the reading comprehension problems. Students had problems in understanding the meaning of new words, feeling anxious and upset were also their problems when they read something in English and cannot understand it. Identifying the aim, no confident, extraction of main and detailed ideas from the text also hindered reading comprehension. Understanding the text's overall meaning and translating every word individually, summarizing the main ideas, distinguishing between the main idea and supporting ideas and stressed were their major reading comprehension problems as well. The findings of the study are essential for English language professors in Afghan EFL classrooms in responding to the problem above. This study proposes that students should be taught reading comprehension strategies such as skimming, scanning, making inferences, looking for main idea, making predictions, improving vocabulary, etc.